(untitled) (Acta Polytechnica CTU Proceedings, 2024)
Self-compacting concrete (SCC) is normally characterized with high pressures exerted on the formwork during casting. The pressures can easily exceed bearing capacity of a regular formwork when casting a high structural member in one step. The contribution shows new ways of reducing the pressures using mineral additives based on calcinated clay minerals and clay nanoparticles whose addition together with interrupted casting process leads to a substantial reduction of the formwork pressures. Short interruptions in the casting lead to microstructural changes and flocculation, thixotropy and early strength evolution. The positive effects are studied systematically in microstructural studies performed on modified cement pastes using microscopy and viscosimetry. Rheological behavior of standard SCCs is improved towards thixotropy of the mixture by using the mineral additives. The newly developed recipes are tested on SCCs used on real construction sites. Examples of their practical utilization and on-site measurements show on up to 50 % pressure reductions in enriched SCCs compared to ordinary SCCs.